Impact of Potassium soil application on growth attributes and yields of Barakawi date palm (Phoenix dactylifera L.) - Elsadig, Elsadig H.; Salih, Fatima D.A.; Idris, Tagelsir I.M.; Jaffar, Mohamed O. (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2021)
The study was accomplished during seasons 2013 and 2014 at two sites, at Al- Bakheet and Hezema villages, Karima locality, Northern State, Sudan. The aim of this study  is to investigate the impact of Potassium sulphate (K2SO4) soil application  on growth attributes, fruit physical traits and yield of "Barakawi" date palm cultivar (Phoenix dactylifera, L.). The selected trees were of uniform growth and size. Four levels of K2SO4 treatments were: 0 (control), 50, 100, and 150g/palm applied in the first season only and their extended effects were also considered in the succeeding season. The study was arranged in a randomized complete block design; where each treatment was replicated four times and data were collected at the harvest time in two seasons. The results showed that the soil application of potassium sulphate at 100g/palm increased number of bunches, bunch weight, and yield (kg) of 'Barakawi' date palm. In addition, the treatments tended to enhance the fruit quality and physical characteristics compared to the control.